Emerging Roles for LGR4 in Organ Development, Energy Metabolism and Carcinogenesis - Yang, Linlin; Wang, Jing; Gong, Xiaodi; Fan, Qiong; Yang, Xiaoming; Cui, Yunxia; Gao, Xiaoyan; Li, Lijuan; Sun, Xiao; Li, Yuhong; Wang, Yudong (Frontiers in Genetics, 2022)
The leucine-rich repeats containing G protein-coupled receptor 4 (LGR4) belonging to G protein-coupled receptors (GPCRs) family, had various regulatory roles at multiple cellular types and numerous targeting sites, and aberrant LGR4 signaling played crucial roles in diseases and carcinogenesis. On the basis of these facts, LGR4 may become an appealing therapeutic target for the treatment of diseases and tumors. However, a comprehensive investigation of its functions and applications was still lacking. Hence, this paper provided an overview of the molecular characteristics and signaling mechanisms of LGR4, its involvement in multiple organ development and participation in the modulation of immunology related diseases, metabolic diseases, oxidative stress damage along with cancer progression. Given that GPCRs accounted for almost a third of current clinical drug targets, the in-depth understanding of the sophisticated connections of LGR4 and its ligands would not only enrich their regulatory networks, but also shed new light on designing novel molecular targeted drugs and small molecule blockers for revolutionizing the treatment of various diseases and tumors.